Pengaruh Budaya Organisasi Syariah Terhadap Produktivitas Kerja Karyawan - Rohmatul Laili, Wakhidah Nur; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2018)
Employees as the main factor certainly have a more important role in the control of an enterprise and operational management. One of the instruments that can improve the quality and expertise of the employee is the culture of sharia organization.This research is a quantitative research which aims to find out how big influence of organizational culture of sharia toward employee work productivity at PT Hasanah Mulia Investama. The results of research conducted with independent variables of sharia organizational culture with work team, integrity, professionalism, tawakkal, responsibility, and care through saturated sampling technique with questionnaire questioning method, it can be concluded that the sharia organization culture in PT Hasanah Mulia Investama as a whole has an effect on productivity employee work.